An optimal strategy on traffic control to regulate street noise over a wide city area from two methodological viewpoints of dynamic programming and maximum principle. (5th August 2014) - Ohta, M.; Hatakeyama, K.; Ikuta, A.; Takaki, N.
The resultant fluctuation patterns of environmental road traffic noise can be principally described by many factors concerning traffic flow and sound propagation. From this point of view, in this paper a new criterion index to emulate the street noise over a wide city area is initially introduced in a functional form related to the Leq evaluation, in close connection with physical parameters of traffic flow and sound propagation characteristics. Then, the optimal control strategies on traffic flow to regulate the street noise over a wide area are generally determined from two methodological viewpoints by use of dynamic programming and maximum principle. Finally, the validity and effectiveness of the proposed method are confirmed, especially by means of digital simulation.